BIOCONVERSION OF PROSOPIS AFRICANA BY SELECTING HIGHER FUNGI THROUGH SOLID-STATE FERMENTATION INTO VALUE-ADDED PRODUCTS - Olarewaju, Victoria Omowumi; Ojo, Tope Julius; Laba, Sunday Ademola (FUDMA Journal of Sciences, 2025)
Agricultural residues such as Prosopis africana pods are abundant yet underutilized due to their high lignocellulosic content and resistance to degradation. This study evaluated their bioconversion through solid-state fermentation (SSF) using Pleurotus ostreatus, Pleurotus pulmonarius, and a mixed inoculum over 28 days. The combined fungal culture achieved the greatest lignin reduction (33.5%) while maintaining the lowest organic matter loss (2.04%), demonstrating efficient nutrient conservation and selective degradation. Proximate composition improved significantly, with crude protein increasing from 8.19% to 10.89% and crude fat also enhanced, while crude fiber declined sharply from 25.17% to 3.4%, indicating improved digestibility. Mineral analysis revealed enrichment of iron and manganese, while reductions in calcium and potassium suggested fungal utilization during metabolism. Fermentation also reduced anti-nutritional factors such as tannins, flavonoids, and phenols, with tannins declining by up to 87%, while secondary metabolites including saponins and terpenoids increased. Lignocellulose degradation was most pronounced in the mixed culture, reflecting synergistic enzyme production and confirming the efficiency of Pleurotus spp. in breaking down complex substrates. Protease activity increased consistently throughout fermentation, correlating with improved protein content and hydrolysis of complex biomolecules. Collectively, these transformations highlight the potential of Pleurotus-based SSF to convert P. africana pods into nutritionally enriched, bioactive-rich, and more digestible products. The synergistic inoculum proved particularly effective, highlighting the application of mixed fungal cultures as a sustainable strategy for developing value-added feed resources from agro-waste.
Keywords: Pleurotus ostreatus; Pleurotus pulmonarius; Prosopis africana; Solid-State Fermentation; Lignin Degradation; Bioconversion; Agro-Waste